Autonomy of will and sustainable consumption in electronic commerce: tensions of colombian law - Calderón Marenco, Eduardo Andrés (DIXI, 2024)
The article addresses a topic of great relevance in the digital age and electronic commerce in Colombia, namely, the tension between two fundamental concepts: autonomy of will and sustainable consumption. The autonomy of will is a legal principle that defends the capacity of parties to establish their own conditions in a contract. In the context of electronic commerce, it implies that consumers have the freedom to choose and purchase products and services online according to their individual preferences. However, this autonomy can conflict with the need to promote sustainable consumption, referring to the practice of consuming consciously, taking into account the environmental and social impact of the products and services acquired. In Colombia, as in many other parts of the world, there is a growing concern for sustainability and environmental protection, which has led to the implementation of regulations and policies aimed at fostering more responsible consumption. The article explores how these two ideas, autonomy of will and sustainable consumption, sometimes clash in the context of Colombian electronic commerce. It examines how Colombian legislation addresses these challenges, identifying possible solutions to balance consumer autonomy with the promotion of more sustainable consumption practices. In summary, the article highlights the importance of finding a balance between consumer autonomy and the need to promote sustainable consumption in Colombian electronic commerce. It also provides a critical view of legal tensions and suggests possible ways to address this dilemma for the benefit of both consumers and the environment.
Keywords: Autonomy of will; electronic commerce; mass contracting; Wrap contracts